Nonequilibrium thermal transport in the two-mode qubit-resonator system - Wang, Fei-Yu; Lu, Jin-Cheng; Wang, Zi; Duan, Li-Wei; Wang, Chen; Ren, Jie (Frontiers in Physics, 2022)
Nonequilibrium thermal transport in circuit quantum electrodynamics emerges as one interdisciplinary field, due to the tremendous advance of quantum technology. Here, we study steady-state heat flow in a two-mode qubit-resonator model under the influence of both the qubit-resonator and resonator-resonator interactions. The heat current is suppressed and enhanced by tuning up resonator-resonator interaction strength with given weak and strong qubit-resonator couplings respectively, which is cooperative contributed by the eigen-mode of coupled resonators and qubit-photon scattering. Negative differential thermal conductance and significant thermal rectification are exhibited at weak qubit-resonator coupling, which are dominated by cycle transition processes. Moreover, the heat flow through the resonator decoupled from the qubit can be dramatically enhanced via the resonator-resonator interaction, which is attributed by the generation of eigen-mode channels of resonators.